SCHOOL PRINCIPAL ACADEMIC SUPERVISION IN IMPROVING THE QUALITY OF LEARNING - Faulina (UNISAN JURNAL, 2024)
The aim of this research is to determine the implementation of supervision in improving the quality of learning at MIN 12 Bandar Lampung. The methodology in this research uses a quantitative approach with causality (cause-effect) research. This research examines and analyzes the implementation of academic supervision in improving joint learning. Based on the discussions that have been carried out in accordance with the main focus of this research, namely improving teacher work through the leadership of MIN 12 Bandar Lampung, it was found that the leadership of the principal of Central Lampung Regency was considered to be good because he had carried out leadership in accordance with the needs of the madrasah organization. The interesting thing about the leadership of school principals in Central Lampung Regency is the inverted pyramid leadership pattern, namely the leader who positions himself as a servant. This has had a significant impact on improving teacher performance in Central Lampung Regency. However, it cannot be denied that the performance of teachers in Central Lampung Regency still needs to continue to be improved so that it is more optimal, especially regarding the three findings mentioned above. It can be concluded that it is not only leadership that is an important factor in improving teacher performance, but there are still various other factors that are also a concern and assessments that must be improved.